Young children's play and creativity : multiple voices - Goodliff, Gill; Canning, Natalie; Parry, John; Miller, Linda (New York, NY : Routledge, 2018)
'This book draws on the voices of practitioners, academics and researchers to examine young children';s play, creativity and the participatory nature of their learning. Bringing together a wide range of perspectives from the UK and internationally, it focuses on the level of engagement and exploration involved in children';s play and how it can be facilitated in different contexts and cultures. This new reader aims to challenge thinking, promote reflection and stimulate further discussion by bringing together research and practice on play and creativity.Divided into two parts, Part ;I is written by researchers and academics and explores key themes such as creative meaning making, listening to children';s voices, risk and spaces, children';s rights, play and technology. Part ;II is authored by Early Childhood professionals and reveals how practitioners have responded to the issues surrounding play and creativity. Each chapter is contextualised by an introduction to highlight the key points and a list of follow-up questions ;is also included to encourage reflection and debate. Drawing on the wide-ranging writing of academics, practitioners and researchers, this book is an invaluable resource for students, practitioners and all those who are interested in the essence of play and creativity, what it means for children, and the far-reaching benefits for their well-being, learning and development.'--Provided by publisher.
'A David Fulton book'--cover.
Includes bibliographical references and index.
Keywords: Play; Creative ability in children; Early childhood education; Child development